Leaders of Polish Political Parties and Their Scope of Power in Party Structures - Tomczak, Łukasz (Political Preferences, 2015)
The purpose of this article is to present the scope of authority of party leaders in selected Polish political parties. The study included the following parties: Civic Platform (PO), Law and Justice (PiS) party, the Democratic Left Alliance (SLD), Polish Peasants’ Party (PSL), Your Movement (TR), Right Wing of the Republic Polish (PR), the New Right (NP) and the Greens. The article addresses the problem of electing a leader of party. The importance of exclusive competence (the powers that belong only to a leader) of the leaders of the Polish party is analyzed. The leader of party may on their grounds decide in certain areas of action of the party. This applies in particular to internal structure, staffing party, the nomination of candidates for election as well as disciplining party members. In most of the subjected parties the leaders have a broad range of rights including the exclusive character. According to the author, some of these powers undermine democratic nature of the party structure. Key words: Polish party system, political party, leader of party, democracy